2002
DOI: 10.1177/000348940211100111
|View full text |Cite
|
Sign up to set email alerts
|

Audiological Assessment in Ramsay Hunt Syndrome

Abstract: Ramsay Hunt syndrome is known to cause symptoms and signs of vestibulocochlear dysfunction, including sensorineural hearing loss. The present study investigates the audiological features of a group of 15 patients with this syndrome. A complete otolaryngological, neurologic, and audiological workup was performed in every patient, including auditory brain stem response measurements and recording of transiently evoked otoacoustic emissions. In most patients, some degree of hearing loss was evident, and abnormal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 26 publications
0
22
0
1
Order By: Relevance
“…Previous investigations of hearing impairment in patients with RHS found that hearing loss in these patients is mild to moderate in most cases, and that cochlear and/or retrocochlear involvement is attributed to this hearing loss. [36] Moreover, while 54% of HZO patients without cochlear symptoms showed hearing loss isolated to high frequency on pure tone audiometry (PTA), only 19% had hearing loss at speech frequency. [4] It was reported that a lesioned site in RHS patients with vertigo may be more likely within the vestibular nerve than the inner ear as a cause for vestibular deficit because the results of vestibular function tests in RHS patients with vertigo were more similar to those in vestibular neuritis patients than those in sudden sensorineural hearing loss with vertigo.…”
Section: Introductionsmentioning
confidence: 99%
“…Previous investigations of hearing impairment in patients with RHS found that hearing loss in these patients is mild to moderate in most cases, and that cochlear and/or retrocochlear involvement is attributed to this hearing loss. [36] Moreover, while 54% of HZO patients without cochlear symptoms showed hearing loss isolated to high frequency on pure tone audiometry (PTA), only 19% had hearing loss at speech frequency. [4] It was reported that a lesioned site in RHS patients with vertigo may be more likely within the vestibular nerve than the inner ear as a cause for vestibular deficit because the results of vestibular function tests in RHS patients with vertigo were more similar to those in vestibular neuritis patients than those in sudden sensorineural hearing loss with vertigo.…”
Section: Introductionsmentioning
confidence: 99%
“…Additionally, an overall reproducibility of 60% was considered necessary for the final pass. Details of TEOAE recordings are described elsewhere (Kaberos, Balatsouras, Korres, Kandiloros, & Economou, 2002). ABR was recorded by three, 6-mm, silver disk recording electrodes attached with and filled with adhesive conductive paste.…”
mentioning
confidence: 99%
“…In this study, all patients with HZO had a CN VII affliction, while 45%, 65%, and 65% of patients had involvement of the cochlear nerve, SVN, and IVN, respectively ( Table 1), which are consistent with a 37% prevalence of cochlear nerve involvement and a 73% prevalence of SVN involvement in the literature. 19,20 In total, 16 (80%) of 20 patients with HZO had an affliction of CN VIII, supporting the fact that both CNs VII and VIII must be assessed. Hence, a test battery of CNs VII and VIII was adopted to register the unaffected nerve bundles.…”
Section: Involvement Of Cns VII and Viiimentioning
confidence: 86%